Facile water oxidation by dinuclear mixed-valence CoIII/CoII complexes: the role of coordinated water. Issue 40 (23rd September 2021) - Dey, Atanu; Guha, Anku; Kumar, Vierandra; Bawari, Sumit; Narayanan, Tharangattu N.; Chandrasekhar, Vadapalli
Abstract : Dinuclear mixed-valence Co III Co II complexes, [Co III Co II (LH2 )2 (X)(H2 O)] (X = OAc or Cl), containing coordinated water show better OER activity than complex [Co III Co II (LH2 )2 (vanillin)] that does not possess coordinated water. Abstract : Rational design of a catalyst using earth abundant transition metals that can facilitate the smooth O–O bond formation is crucial for developing efficient water oxidation catalysts. The coordination environment around the metal ion of the catalyst plays a pivotal role in this context. We have chosen dinuclear mixed-valence Co III Co II complexes of the general formula of [Co III Co II (LH2 )2 (X)(H2 O)] (X = OAc or Cl) which bear a coordinated water molecule in the primary coordination sphere. We anticipated that the water molecule in the primary sphere can take part in the proton coupled electron transfer (PCET) mechanism which can accelerate the facile formation of the O–O bond under strong alkaline conditions (1 M NaOH). To understand the role of the coordinated water molecule we have generated an analogous complex, [Co III Co II (LH2 )2 ( o -vanillin)] ( o -vanillin = 2-hydroxy-3-methoxybenzaldehyde), without coordinated water. Interestingly, we have found that the water coordinated complexes show better oxygen evolution reaction (OER) activity and stability.